Association between ABO blood group and unfavorable prostate cancer features after radical prostatectomy: Retrospective study of 1149 patients. (31st December 2022) - Porcaro, Antonio Benito; Amigoni, Nelia; Rizzetto, Riccardo; Migliorini, Filippo; Tafuri, Alessandro; Piccoli, Pierluigi; Tiso, Leone; De Michele, Mario; Bianchi, Alberto; Gallina, Sebastian; Ornaghi, Paola Irene; Orlando, Rossella; et al.
Abstract: Objectives: To test hypothesized associations between the ABO blood group (ABO-bg) system and the pathological features of prostate cancer (PCa). Material and methods: Between January 2013 and September 2019, 1173 patients underwent radical prostatectomy. Associations between ABO-bg levels and pathological features were evaluated using statistical methods. Results: Overall, 1149 consecutive patients were evaluated using the ABO-bg system, which was represented by O-bg (42.8%) and A-bg (41.3%), followed by B-bg (11.1%) and AB-bg (4.8%). Only positive surgical margins (PSMs) was correlated with ABO-bg (Pearson correlation coefficient, r = 0.071; p = 0.017), and the risk was increased in group-O (odds ratio [OR], 1.497; 95% confidence interval, 1.149–1.950; p = 0.003) versus non–O-bg. In clinical and pathological models, O-bg was at increased risk of PSM after the adjustment for prostate-specific antigen, percentage of biopsy-positive cores, and high surgical volume (adjusted OR, 1.546; 95% confidence interval, 1.180–2.026; p = 0.002); however, the adjusted OR did not change after the adjustment for tumor load and stage as well as high surgical volume. Conclusions: In clinical PCa, the risk of PSM was higher in O-bg versus non–O-bg patients after the adjustment for standard predictors. Confirmatory studies are needed to confirm the association between ABO-bg and unfavorable PCa features.